REVENGE AND ITS IMPACT TO PERSONALITY IN GILLES PIE’S CRUELLA (2021): A PSYCHOLOGICAL PERSPECTIVE - Anjani, Berliana; Thoyibi, Mohammad (Universitas Negeri Makassar, 2024)
The aim of this research is to analyze the psychological state of revenge against the main character Estella (Cruella) in the film Cruella. This research uses qualitative methods to analyze several resolved events. This research uses a qualitative descriptive analysis method. The data source for this research is the film Cruella by Craig Gillespie. The research results show that there are 4 indicators of Cruella's revenge, namely feeling lost, character transformation, creating competition, and manipulation of the situation. There are 4 factors that show revenge in the film Cruella, namely characteristics, setting, plot, and style. The film uses a dynamic combination of sound and visual effects to create a visually stunning and immersive cinematic experience that transports audiences into the colorful and bold world of his iconic roles.